Cork-oak woodlands as key-habitats for biodiversity conservation in Mediterranean landscapes: a case study using rove and ground beetles (Coleoptera: Staphylinidae, Carabidae) (Biodiversity and Conservation, 2008)
Land-use intensiﬁcation in Mediterranean agro-forest systems became a pressure on biodiversity, concerning particularly the woodland sensitive species. In 2001, the effects of a land-use gradient from old-growth cork-oak forest to a homogeneous agricultural area were assessed using rove beetles as indicators in a Mediterranean landscape. The aim was to ﬁnd which species were negatively affected by land-use intensiﬁcation at the landscape level and whether they beneﬁted from cork-oak patches occurring along the land-use gradient. A total of 3,196 rove beetles from 88 taxa were sampled from all landscape types. Agricultural area recorded signiﬁcantly higher numbers of abundance and species richness in relation to the cork-oak mosaics, i.e. the old-growth forest and the managed agro-forest landscapes (montados). Moreover, 70% of rove beetle indicator species common enough to be tested by IndVal displayed their highest indicator value for agriculture, showing a lower number of woodland indicators in comparison to ground beetles. Nevertheless, one rove beetle taxon was considered a specialist of closed woodland mosaics while no specialist ground beetle was found for that landscape typology. Some rare rove beetle species were also important in typifying diversity patterns of oldgrowth cork-oak forests. Hence, future management in Mediterranean landscapes should take into account not only indicator species common enough to be tested by IndVal, but also rare and endemic species. Considering the added value of cork-oak woodland cover for sensitive rove and ground beetle diversity, the strengthening of cork-oak woodland connectivity seems to be a crucial management that is required in agricultural Mediterranean landscapes.

Cork-oak woodlands as key-habitats for biodiversity conservation in Mediterranean landscapes: a case study using rove and ground beetles (Coleoptera: Staphylinidae, Carabidae) - Silva, Pedro Martins; Aguiar, Carlos a S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M.; da Silva, Pedro Martins; Aguiar, Carlos a S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M. (Biodiversity and Conservation, 2008)
Land-use intensiﬁcation in Mediterranean agro-forest systems became a pressure on biodiversity, concerning particularly the woodland sensitive species. In 2001, the effects of a land-use gradient from old-growth cork-oak forest to a homogeneous agricultural area were assessed using rove beetles as indicators in a Mediterranean landscape. The aim was to ﬁnd which species were negatively affected by land-use intensiﬁcation at the landscape level and whether they beneﬁted from cork-oak patches occurring along the land-use gradient. A total of 3,196 rove beetles from 88 taxa were sampled from all landscape types. Agricultural area recorded signiﬁcantly higher numbers of abundance and species richness in relation to the cork-oak mosaics, i.e. the old-growth forest and the managed agro-forest landscapes (montados). Moreover, 70% of rove beetle indicator species common enough to be tested by IndVal displayed their highest indicator value for agriculture, showing a lower number of woodland indicators in comparison to ground beetles. Nevertheless, one rove beetle taxon was considered a specialist of closed woodland mosaics while no specialist ground beetle was found for that landscape typology. Some rare rove beetle species were also important in typifying diversity patterns of oldgrowth cork-oak forests. Hence, future management in Mediterranean landscapes should take into account not only indicator species common enough to be tested by IndVal, but also rare and endemic species. Considering the added value of cork-oak woodland cover for sensitive rove and ground beetle diversity, the strengthening of cork-oak woodland connectivity seems to be a crucial management that is required in agricultural Mediterranean landscapes.
Keywords: á; agro-forest mosaic; agro-forest mosaic á biodiversity; Biodiversity conservation; conservation á epigaeic coleoptera; epigaeic coleoptera; indicator value; indicator value á land-use; intensification á quercus suber; land-use intensification; Quercus suber